Analisis Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2017-2021 - Rachma Nugraha, Adhitya; Soebagyo, Daryono (Fakultas Ekonomi Universitas Gresik, 2023)
The role of the government in setting strategies to encourage the process of economic growth is very important, one of the strategies used by the government in Indonesia is fiscal decentralization. Fiscal decentralization is the granting of authority from the central government to regional governments to regulate their own territory. This research pays attention to the effect of profit-sharing funds, general allocation funds, special allocation funds, and profit-sharing funds on economic growth in Indonesia by using panel data regression analysis. Based on the results of panel data regression analysis in Indonesia during the 2017-2021 period, it shows that profit-sharing funds, general allocation funds have a positive influence on economic growth. Meanwhile, special allocation funds have a negative and significant impact on economic growth